Evaluation of CTLA-4, CD28 and CD86 Genes Polymorphisms in Acute Renal Allograft Rejection among Tunisian Patients - Krichen, Henda; Sfar, Imen; Abdallah, Taieb Ben; Bardi, Rafika; Abderrahim, Ezzeddine; Jendoubi-Ayed, Saloua; Makhlouf, Mouna; Aouadi, Houda; Ayadi, Hammadi; Ayed, Khaled; Gorgi, Yousr (IntechOpen, 2011)
None